EMPLOYEE LOYALTY MEDIATING THE INFLUENCE OF WORK LIFE BALANCE AND FINANCIAL COMPENSATION TOWARDS EMPLOYEE PERFORMANCE - Putu Ayu Rias Yudiani; I Putu Santika; I Ketut Mustika (Sean Institute, 2023)
The research was conducted regarding the mediating role of employee loyalty in work-life balance and financial compensation for employee performance at PT. BPR Regional Bank Bangli (Perseroda). Sampling technique through saturated sampling. The sample used is 71 employees at PT. BPR Regional Bank Bangli (Perseroda). The type of data is quantitative data with data sourced from primary sources. Data analysis was performed using Partial Least Square (PLS). The results show that Work-Life Balance, financial compensation, and employee loyalty significantly positively affect employee performance. Work-Life Balance does not affect employee loyalty, financial compensation has a significant positive effect on employee loyalty, employee loyalty has not been able to mediate the impact of Work-Life Balance on employee performance, and employee loyalty can mediate financial compensation on employee performance.